A comparison between cactophilic yeast communities isolated from Cereus hildmannianus and Praecereus euchlorus necrotic cladodes. Issue 10 (October 2016) - Camargo, Franciele Pereira; Araujo, Ana Carolina Vieira; Moraes, Evandro Marsola de; Dos Santos, André Cordeiro Alves
Abstract: In the cactus-yeast- Drosophila model system, the necrotic cladode is used as substrate by a diverse and specific microbiota, which is utilized as food source by Drosophila . Although this association has been the focus of many studies in arid regions of North America, little is known of its composition in South America. This study analysed yeast communities isolated from two South American cacti species: Cereus hildmannianus and Praecereus euchlorus . Fourteen yeast species were isolated and identified by their morpho-physiological character and partial rRNA gene sequencing. Arthropods hatched from the analysed cladodes were identified. There was little similarity between the isolated yeast communities either in terms of cacti species (S = 0.286) or collection sites (S = 0.214–0.335). To the best of the authors' knowledge, this is the first time that Metschnikowia koreensis and Hannaella sinensis have been described in association with cacti. Also, Drosophila buzzatti has not been described in association with Praecereus . The similarity between cactophilic arthropod communities found in the different cacti was low (S = 0.266) and zero when only Drosophila was considered. These results suggest that exploration by Drosophila species is the main factor that drives low yeast community similarity between cacti species. Highlights: The first time that Metschnikowia koreensis was associated with cacti. The first time that Hannaella sinensis was associated with cacti. The first time that Drosophila buzzatti was associated with Praecereus. The main factor in driving low yeast community similarities in cacti species.